Excess Body Weight and the Risk of Liver Cancer: Systematic Review and a Meta-Analysis of Cohort Studies. (2nd October 2020) - Yang, Chao; Lu, Yifei; Xia, Hui; Liu, Hechun; Pan, Da; Yang, Xian; Sun, Guiju
Abstract: Objective: To update and expand the previous meta-analysis including all prospective studies on the issue of the associations between overweight, obesity, and liver cancer risk. We also performed a meta-regression to investigate a potential nonlinear and/or linear association between body mass index (BMI) and liver cancer risk. Methods: Literature search was conducted in four libraries from the beginning of indexing for each database to 1st September, 2018. Results: The summary risk estimate was statistically significant on the association between overweight and the risk of liver cancer incidence (relative ratio [RR] = 1.19). The RRs were significantly stronger in people with known liver disease with overweight than in the general population with overweight (RR = 1.50 vs. RR = 1.10; P difference  = .02). The meta-analysis showed an increase by 87% on the risk of liver cancer incidence in obesity categories, relative to categories of normal BMI (RR = 1.87, P  < .01). Moreover, the results showed that, overweight was associated with 9% increased and obesity with 66% increased for risk of liver cancer mortality. In linear model, the relative risks of liver cancer were 1.32 for continuous BMI per 5 kg/m 2 increase. Conclusion: This meta-analysis supports the hypothesis that overweight, obesity may significantly increase liver cancer risk.